HLA-B27 homodimers and free H chains are stronger ligands for leukocyte Ig-like receptor B2 than classical HLA class I. - Giles, J; Shaw, J; Piper, C; Wong-Baeza, I; McHugh, K; Ridley, A; Li, D; Lenart, I; Antoniou, A; DiGleria, K; Kuroki, K; Maenaka, K; et al. (2012)
Possession of HLA-B27 (B27) strongly predisposes to the development of spondyloarthritis. B27 forms classical heterotrimeric complexes with β(2)-microglobulin (β2m) and peptide and (β2m free) free H chain (FHC) forms including B27 dimers (termed B27(2)) at the cell surface. In this study, we characterize the interaction of HLA-B27 with LILR, leukocyte Ig-like receptor (LILR)B1 and LILRB2 immune receptors biophysically, biochemically, and by FACS staining. LILRB1 bound to B27 heterotrimers with a K(D) of 5.3 ± 1.5 μM but did not bind B27 FHC. LILRB2 bound to B27(2) and B27 FHC and B27 heterotrimers with K(D)s of 2.5, 2.6, and 22 ± 6 μM, respectively. Domain exchange experiments showed that B27(2) bound to the two membrane distal Ig-like domains of LILRB2. In FACS staining experiments, B27 dimer protein and tetramers stained LILRB2 transfectants five times more strongly than B27 heterotrimers. Moreover, LILRB2Fc bound to dimeric and other B27 FHC forms on B27-expressing cell lines more strongly than other HLA-class 1 FHCs. B27-transfected cells expressing B27 dimers and FHC inhibited IL-2 production by LILRB2-expressing reporter cells to a greater extent than control HLA class I transfectants. B27 heterotrimers complexed with the L6M variant of the GAG KK10 epitope bound with a similar affinity to complexes with the wild-type KK10 epitope (with K(D)s of 15.0 ± 0.8 and 16.0 ± 2.0 μM, respectively). Disulfide-dependent B27 H chain dimers and multimers are stronger ligands for LILRB2 than HLA class I heterotrimers and H chains. The stronger interaction of B27 dimers and FHC forms with LILRB2 compared with other HLA class I could play a role in spondyloarthritis pathogenesis.